A study of the composition of combustible waste in urban area of Rovaniemi - Savela, Rita (2024)
The work was commissioned by Napapiirin Residuum Oy and the topic was composition study of combustible waste in their operating area in Rovaniemi. The aim of this bachelor’s thesis was to find out the composition of a regular Rovaniemi household’s combustible waste bag by manually sorting through samples of combustible waste. The amounts of biowaste and packaging materials were additional points of interest. The practical implementation of the study was conducted in Napapiirin Residuum Oy facilities in February of 2024. Suomen Kiertovoima ry’s guide to composition study of mixed waste was used as a guide in planning and implementation of the practical part. Volunteers from Lapland Education Centre were asked to join the manual sorting process. The study shows that the composition of a regular Rovaniemi household’s waste bag includes large amounts of biowaste, paper and plastic. This correlates with the national average in Finland in 2023. Based on the results, it is clear that the enhanced separate collection according to the amendment of Waste Act, especially on biowaste, is a necessary change to our waste management to reach recycling rate targets. For households, a change in attitudes and practices is needed to improve the composition of combustible waste and advancing sustainable development